Stakeholder Theory in Action, The Impact of ESG Practices on Financial Performance in SADC Region Food Producers - Şahin, Arzu; Mitawa, Walid Khalid (Cumhuriyet Üniversitesi iktisadi ve idari bilimler dergisi, 2025)
In recent years, there has been a notable shift towards incorporating non-fincancial metrics, particularly environmental, social, and governance (ESG) factors, into the corporate financial performance (CFP) evaluation framework. The primary aim of this research is to explore the impact of ESG practices on corporate financial performance, with a particular focus on the Southern African Development Community (SADC) region, which is frequently underrepresented in global ESG debates. The study concentrates on the food production sector, a key industry for this region. To achieve this aim, after the theoretical background on the subject, the empirical section examines whether engagement in ESG practices contributes to financial performance, measured primarily by Tobin's Q and alternatively by the market-to-book value ratio. The panel data models are employed for 8-year panel data of 32 publicly traded food producer companies of the SADC region between 2015 and 2022. Additionally, for the robustness test, the analysis is also repeated on a subset of 14 food producers listed in South Africa. According to the analysis results, companies disclosing ESG practices and so having an ESG score operate with higher Tobin Q and market-to-book value ratio, across both the SADC and South Africa samples. The findings suggest that companies actively involved in social, environmental, and governance initiatives, alongside transparent disclosure of their responsible practices, tend to exhibit superior financial performance. This finding is consistent with stakeholder theory, suggesting that firms can only enhance their long-term financial performance by fulfilling their responsibilities to all stakeholders and, ultimately, to society.